PENGARUH PENYINARAN LAMPU TL MERAH BIRU TERHADAP PERTUMBUHAN BIBIT NANAS (Ananas comosus) HASIL HIBRIDISASI - Retno Dwi Andayani (Universitas Islam Kadiri, 2016)
This experiment aims to review the combining effect of irradiating red and blue light, and irradiating period on the pineapple seeds. Seeds derived from the pineapple seed that comes from a pineapple cross .Research has carried out in december 2015 to march 2016 in research and development nursery, Great Giant Pineapple Company, Terbanggi Besar, Lampung Tengah .The hypothesis research are irradiating lights able to develop seeds growth and irradiating period will be triggered seeds faster and also know which lights precise accordance with the seeds growth .The lights used in research is a combination lights were in red and blue. The first combination is the Neon light Red-Blue-Red ( hereinafter called dominant red light), and the second combination is Neon light Blue-Red-Blue ( hereinafter called dominant blue light). The research uses random design groups and continue with orthogonal contrast analysis with 3 replication , so there are 51 treatment combination.The characters observed in research are seeds height , the number of leaves , the wide of leaves , the weight of seeds and chlorophyll levels . The result showed that irradiating with dominan red lightor blue light, they can improve almost all character observed in research except seeds height.In general, the longer duration irradiating the more improve the result of the character observed. Irradiating dominant red light and blue lighton many irradiating duration proven capable of accelerating growth pineapple seedling derived from the seed. For vegetative character, irradiating ofdominant red lights with irradiating period 24 hours, is best treatment to stimulate seeds growth.While to increase levels of chlorophyll , irradiating dominant blue light with irradiating period 24 hours is the best treatment.